Pengaruh Kualitas Pelayanan dan Citra Perusahaan terhadap Kepuasan Nasabah Kredit pada LPD Desa Adat Guwang - Erwin, I Wayan; Sadiatha, A. A. Ngurah Gede; Purwaningrat, Putu Atim (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Credit customer satisfaction is a perception of a customer that if his wishes are fulfilled properly or according to his will. To achieve customer satisfaction, it is necessary to have good service quality and a good corporate image. This study aims to determine the effect of service quality and corporate image on customer satisfaction. The research was conducted at the Guwang Traditional Village LPD, Sukawati, Gianyar. The number of samples used in this study amounted to 90 respondents taken by the Acidental Sampling method. Validity and reliability tests were used to test research instruments. The analysis technique used is the classical assumption test, multiple linear regression analysis, determination analysis, t test and F test. Based on the results of the study, it can be seen that service quality has a positive and significant partial effect on credit customer satisfaction at LPD Guwang Traditional Village. Corporate image has a partial positive and significant effect on credit customer satisfaction at the Guwang Traditional Village LPD. And service quality and corporate image simultaneously have a positive and significant effect on credit customer satisfaction at the Guwang Traditional Village LPD.